Egg reappearance periods associated with anthelmintic treatments given to horses in winter and summer over two years - Scott I; Lawrence KE; Gee EK (Elsevier B.V., 2024)
Shortened egg reappearance periods (ERP) have been seen as an early warning of anthelmintic resistance development in cyathostomins in horses. The hypothesis has been that in these instances, efficacy against egg laying adult cyathostomins remains high, but a decline in activity against later larval stages leads to the earlier resumption of egg shedding after treatment. In this study using a single herd of horses we investigated the ERP of a number of commonly used equine anthelmintics and examined whether ERP might show seasonal variation between winter and summer. Four main Faecal egg count reduction tests (FECRT1–4) were conducted respectively in Winter (Jun/Jul) 2019, Summer (Jan/Feb) 2020, Winter 2020 and Summer 2021. The tests examined the efficacy and ERP of ivermectin, moxidectin, abamectin and fenbendazole. Egg counts of two groups of horses were monitored before and for 6–7 weeks after treatment - however long it took for counts to return to at least 10 % of what they had been before treatment. One additional FECRT was also conducted, using a second abamectin-containing product (FECRT5 - Spring 2020). Treatment with ivermectin (FECRT1–4), moxidectin (FECRT 1–2) and the first abamectin product tested (FECRT3) all reduced egg counts by >99 % for 4 weeks after treatment, with ERP of 5–7 weeks and with minimal differences between the 3 treatments. There was a tendency for counts to rise more rapidly in summer, and in the second year of testing as opposed to the first. Both the second abamectin product (FECRT5) and the fenbendazole (FECRT4) were found to be ineffective, reducing egg counts immediately after treatment by 68 and 52 % respectively.
Keywords: Egg reappearance period; Ivermectin; Abamectin; Moxidectin; Fenbendazole; Horses; Egg counts